2007
DOI: 10.7326/0003-4819-147-9-200711060-00008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Stable Chronic Obstructive Pulmonary Disease: A Clinical Practice Guideline from the American College of Physicians

Abstract: RECOMMENDATION 1: In patients with respiratory symptoms, particularly dyspnea, spirometry should be performed to diagnose airflow obstruction. Spirometry should not be used to screen for airflow obstruction in asymptomatic individuals. (Grade: strong recommendation, moderate-quality evidence.) RECOMMENDATION 2: Treatment for stable chronic obstructive pulmonary disease (COPD) should be reserved for patients who have respiratory symptoms and FEV1 less than 60% predicted, as documented by spirometry. (Grade: str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
392
1
30

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(428 citation statements)
references
References 48 publications
5
392
1
30
Order By: Relevance
“…This observation differed from that of a previous study involving general subjects in Japan who showed a similarly high prevalence of COPD (20). However, it could not be concluded from the present data whether spirometry should be performed to diagnose airflow obstruction in patients with exertional dyspnea (21), because the prevalence of subjects who complained of dyspnea was high throughout the 4 years of study I as well as in the 1-day screening used in study II. The present study suggests that advanced screening using a questionnaire system could be more effective than spirometry for COPD screening.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation differed from that of a previous study involving general subjects in Japan who showed a similarly high prevalence of COPD (20). However, it could not be concluded from the present data whether spirometry should be performed to diagnose airflow obstruction in patients with exertional dyspnea (21), because the prevalence of subjects who complained of dyspnea was high throughout the 4 years of study I as well as in the 1-day screening used in study II. The present study suggests that advanced screening using a questionnaire system could be more effective than spirometry for COPD screening.…”
Section: Discussioncontrasting
confidence: 99%
“…As none of the control subjects in this study had respiratory problems or lung diseases or were receiving inhaled bronchodilators or corticosteroids, spirometry in this group was not conducted, in accordance with the guidelines of the American College of Physicians, American College of Chest Physicians, ATS, and ERS. 34 All subjects with COPD were stable, and 77% were non-admitted out-patient cases visiting the hospital for routine checkups and free medicines. The remaining 23% of subjects with COPD were admitted to the Cardio-Thoracic Centre for other causes.…”
Section: Resultsmentioning
confidence: 99%
“…However, with respect to mucolytics and airway clearance, dornase alfa is not recommended for patients with non-CF bronchiectasis. 15,16 Trials with clinically important outcome measures are needed to establish the evidence for mucoactive medications outside of CF. 17…”
Section: Hospitalized Adult and Pediatric Patients Without Cystic Fibmentioning
confidence: 99%